Significance of SSI and non-uniform near-fault ground motions in bridge response II: Effect on response with modular expansion joint - Chouw, N.; Hao, Hong (Pergamon, 2008)
This is the second part of the study of soil-structure interaction (SSI) and ground motion spatial variation effects on bridge pounding responses. The first part [Chouw N, Hao H. Significance of SSI and non-uniform near-fault ground motions in bridge response I: Effect on response with conventional girder gap. J Eng Struct. [in press]] concentrated on studying the responses of bridges with a traditional expansion joint between adjacent girders. The main objective of this second paper is to investigate the influence of spatial variation of ground motions and SSI on the minimum total gap that a modular expansion joint system (MEJS) between two bridge frames must have to prevent any pounding between the adjoined girders. This minimum total gap is critical in a MEJS design because it ensures intact expansion joint and adjacent girders. Additional investigations of pounding response with a large total gap of a MEJS are performed to study the characteristics of pounding responses when collision does occur e.g. due to unintended underestimation of the ground excitation magnitude, which may be different from the pounding responses between bridge girders with a small gap of a conventional expansion joint. The spatially varying ground excitations are simulated stochastically based on an empirical near-source response spectrum and an empirical coherency loss function. The investigation reveals that neglecting spatial variation of ground motions and SSI can significantly underestimate the total gap of a MEJS required to avoid pounding between the adjacent bridge girders. The results also show that pounding between girders with a large gap of a MEJS in general causes stronger impact forces. Compared with the results reported in the first part of this study, using a MEJS with a large gap is likely to completely preclude bridge girder pounding, and consequently to prevent local damage at the girder ends. However, a large girder movement results in large bending moment in bridge piers, which compensates the advantages of using MEJS in bridges to resist earthquake loading.